CAPITAL MARKET TRADING BEHAVIOUR WITHIN CRISIS PERIOD - Bramantyo Djohanputro (Universitas Gunadarma, 2012)
This paper aims at exploring the investors’ behavior on investment decisions, especially on how they express their daily behavior in considering trading volume, market returns, and market volatility in their trading or investment decisions within the crisis period as the impact of the subprime mortgage crisis in the United States of America. They are expected to employ current and past information contained in trading volume, returns, and volatility, in their decision making under market pressure because of crisis. To explore those relationships, regressions with Autoregressive Conditional Heteroskedasticity, or ARCH, are employed. More specifically, TARCH model is applied to explore the possibility of asymmetric response of negative and positive information. The study reveals that traders are more concerned with volatility than with return within the crisis period. Also, they tend to behave differently to different types of information, i.e. negative and positive information. Keywords: return, volatility, volume, TARCH, asymmetry